Exploring Social Studies Education Through the Lens of Constructivism: A Literature Review (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This study explores the efficacy of the constructivist approach in Social Studies (IPS) education, investigating its role in shaping the learning landscape. IPS, a blend of social sciences tailored for educational purposes, becomes a focal point as constructivism emerges as a theoretical framework. Defined as a cognitive process based on students' experiences, constructivism emphasizes active knowledge construction. The research employs a literature review methodology, analyzing trends from articles published from 2019 to 2023. The findings underscore the positive impact of implementing constructivism in IPS education, fostering heightened student engagement, motivation, and improved academic achievement. This study offers insights for educators and researchers seeking to enhance student-centric learning strategies in the dynamic realm of IPS education.